2022
DOI: 10.3389/fnut.2022.888191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation With Clostridium butyricum on Growth Performance, Apparent Digestibility, Blood Metabolites, Ruminal Fermentation and Bacterial Communities of Fattening Goats

Abstract: Clostridium butyricum (C. butyricum) is currently widely used to improve the body health and productive performance of monogastric animals. However, there have been few reports on the effects and specific mechanism of action of Clostridium butyricum in ruminants. This study aimed to investigate the effects of Clostridium butyricum supplementation on the growth performance and digestive microbiota of fattening goats. Twenty-four healthy male Albas goats (body weight = 22 ± 2.03 kg) were randomly divided into 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…However, it was found in this experiment that supplementation with different forms of C. butyricum had no significant effect on the expression of TNF -α, IL-1 β, IL-6 , and IL-10 in the intestinal tract of goats. This may be related to our previous study that supplementation with C. butyricum failed to alter nutrient metabolism in goats, resulting in no significant changes in daily weight gain and feed efficiency ( Zhang C. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, it was found in this experiment that supplementation with different forms of C. butyricum had no significant effect on the expression of TNF -α, IL-1 β, IL-6 , and IL-10 in the intestinal tract of goats. This may be related to our previous study that supplementation with C. butyricum failed to alter nutrient metabolism in goats, resulting in no significant changes in daily weight gain and feed efficiency ( Zhang C. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 68%
“…The current study aimed to describe how dietary supplementation with C. butyricium affects the intestinal tract’s health by adapting the goats’ microbial community. Our previous research indicated that different doses of C. butyricium could modulate beneficial microbial diversity and relative abundance in the rumen and feces of fattening goats ( Zhang C. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that supplementation of CB in the diets had an effect on the modulation of bacterial communities in the feces of weaned piglets ( Liang et al, 2021 ), intestine of chickens ( Huang et al, 2019 ), or rumen and rectum of goats ( Zhang et al, 2022 ). In the present study, the relative abundances of five phyla (10 in total) and 12 genera (27 in total) were changed with the supplementation of CB, which may be due to the nutritional factors that change with supplementation ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous trial’s results showed that high-concentrate dietary supplementation with C. butyricum could influence the production and transport of volatile fatty acid in the rumen by regulating the structure of rumen microbiota to stabilize the rumen pH and improving the persistent effect of feeding high-concentrate diets on the rumen of fattening goats in the short term ( 16 ). In the meantime, we found that C. butyricum could reach the intestine through the rumen and enhanced the intestinal epithelial barrier function of goats by regulating the intestinal microbial community ( 17 ).…”
Section: Introductionmentioning
confidence: 99%